ANALYSIS OF PARTICIPANTS’ SATISFACTION UNDER CONTRACT FARMING: A CASE OF PEANUT FARMING IN LOMBOK ISLAND - I Gusti Lanang Parta Tanaya (UNEJ e-Proceeding, 2012)
Contract farming is expected to reduce asymmetric information and price uncertainty of products. In partnership of peanut farmers with PT Bumi Mekar Tani (BMT) in Lombok, contract farming is intended to increase the performance of supply chain. Farmers may be interested in entering into the contract if it guarantees them to have better benefit. After two years running this contract farming, there is no evaluation about participant’s satisfaction and about the performance of peanut supply chain. This paper reports participants’ satisfaction in conducting their business under the contract and the performance of peanut supply chain. Data were collected based on semi-structured questionnaire and analyzed using Customer Satisfaction Index and Importance Performance Analysis. Descriptive and Factor Analysis are used to understand supply chain performance and its significant factors. The results show most farmers satisfy on the partnership with BMT and the performance of supply chain becoming better. The study also revealed that the socio traditional value of the villagers coloured the relationship between farmers and their product buyers.